2010
DOI: 10.1186/1471-2334-10-84
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant glycerol is not beneficial in experimental pneumococcal meningitis

Abstract: BackgroundBacterial meningitis in children causes high rates of mortality and morbidity. In a recent clinical trial, oral glycerol significantly reduced severe neurological sequelae in paediatric meningitis caused by Haemophilus influenzae type b, and a tendency towards a benefit of adjunctive glycerol was seen in pneumococcal meningitis.MethodsHere we examined the effects of glycerol in pneumococcal meningitis of infant rats and adult mice. All animals received ceftriaxone, and glycerol or placebo. Brain dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Matrix metalloproteinase-9 (MMP-9) concentrations in CSF were significantly lower in glycerol-treated rats at 40 h after infection. This difference in MMP-9 in late disease did not result in an improvement of histopathologic parameters [133], that is, no clear beneficial effect of glycerol could be demonstrated in animal models of bacterial meningitis.…”
Section: Glycerol and Other Intracranial Pressure-lowering Agentsmentioning
confidence: 97%
“…Matrix metalloproteinase-9 (MMP-9) concentrations in CSF were significantly lower in glycerol-treated rats at 40 h after infection. This difference in MMP-9 in late disease did not result in an improvement of histopathologic parameters [133], that is, no clear beneficial effect of glycerol could be demonstrated in animal models of bacterial meningitis.…”
Section: Glycerol and Other Intracranial Pressure-lowering Agentsmentioning
confidence: 97%
“…128 However, to date, there is insufficient clinical or experimental evidence to support glycerol therapy for BM. 141,142 …”
Section: Glycerol Therapymentioning
confidence: 98%
“…To date, however, little is known about possible interactions between ceftriaxone and MMPs since current experiments are mainly on rodent models of meningitis experimenting the effect of other MMP inhibitors (e.g. Ro 32-3555 or GM6001) on neuronal loss or learning abilities with ceftriaxone only as a comedication [31,32,33,34,35,36,37]. Since studies on minocycline show a 2-fold decrease and ceftriaxone in current analysis showed a 3-fold increase in post-IVT-sICH rate, an identical effect of ceftriaxone on MMPs seems unlikely.…”
Section: Discussionmentioning
confidence: 99%